X-ray diffraction of ions in aqueous solutions : hydration and complex formation /: hydration and complex formation. (2018) - Magini, Mauro; Licheri, Giovanni; Paschina, Giorgio; Piccaluga, G (Giorgio); Pinna, Gabriella
No abstract available